Reactivity of Intermediates - From synthetic applications of hydroxycarbenes towards telluryl radicals in organic chemistry - Keul, Felix; Justus Liebig University Giessen (My University, 2022)
Hydroxycarbenes (R−C̈ C̈ −OH) were only theoretically known for a long time and postulated as intermediates in many reactions. Until 2008 only stabilized hydroxycarbenes by metal complexes as Fischer- and Schrock-carbenes are known. Schreiner et al. used matrix isolation methods to trap a free hydroxycarbene near absolute zero. Even at these low temperatures hydroxycarbenes turned out as not persistent and reacted by quantum mechanical tunneling (QMT) towards the corresponding aldehydes. Starting from the initial work in 2008 about the simplest hydroxycarbene, hydroxymethylene (H−C̈ C̈ −OH),), in the following decade a lot of derivatives were isolated and studied. The first publication deals with the generation of free hydroxycarbenes in solution and the proof of the existence of their reaction products. A modified McFadyen-Stevens precursor was used to generate phenylhydroxycarbene under the cleavage of a tosyl-group and nitrogen extrusion. Phenylhydroxycarbene was trapped by benzaldehyde and acetone in a so-called carbonyl-ene reaction and the formation of the resulting acetoins is proven via NMR spectroscopy. The second part of this thesis is about tellurium radicals. These come up with a broad spectrum of applications and are used in cross-couplings and trans-metalations as well as in industrial polymer chemistry. The group of Yamago started to study organotellurium compounds and their application in polymer chemistry in the early 2000s but the used tellurium radicals were never isolated and studied before. In the second and third publications organotellurium radicals, namely phenyltelluryl radical and vinyltelluryl radical, are isolated and their properties and reactivities are described. We used the corresponding dimers to isolate them in an inert solid argon matrix and studied their stability and reaction with molecular oxygen. While the phenyltelluryl radical proves to be stable under matrix isolation conditions, the vinyltelluryl radical rearranges under photoirradiation towards an acetylene-TeH-radical complex. In reaction with molecular oxygen both behave identically. In a barrierless reaction, they primarily form a hyperoxide which isomerizes towards a dioxide.
Keywords: ddc:540